Analysis of the Impact of Special Autonomy Fund Allocation on Human Development Index in Papua Province 2017-2022 - Azzahra, Fadia (Urecol Journal. Part B: Economics and Business, 2023)
The gap that occurs between Papua Province and other provinces in Indonesia has led the central government to provide special autonomy funds to Papua Province. The funds are used to accelerate development in Papua Province, one of which is in terms of human development. However, in reality, Papua Province remains the province with the lowest Human Development Index in Indonesia. Therefore, this study aims to examine the impact of the allocation of special autonomy funds on the Human Development Index in Papua Province in 2017-2022. The method used in this research is a qualitative method with data sources in the form of secondary data. The results of this study indicate that the special autonomy fund has no significant impact on HDI in Papua Province in 2017-2022. The amount of special autonomy funds received by Papua Province does not affect the magnitude of the increase in HDI. Problems such as education and health are homework that must be considered by the Papua Government to improve HDI in the region. The Papua government needs to make clear details, targets, and programs for the use of special autonomy funds.